IX з’їзд Громадської організації “Українське ентомологічне товариство” (загальний огляд роботи з’їзду, звіт ревізійної комісії, Рада ГО «УЕТ», резолюція) - Puchkov, O. V.; Kaliuzhna., M. O.; Fedorenko, V. P.; Shatrovsky, О. G.; Korneev, V. O.; Meshkova, V. L. (public organization "Ukrainian Entomological Society", I.I. Schmalhausen Institute of Zoology of National Academy of Sciences of Ukraine, Institute of Plant Protection of National Academy of Agrarian Sciences of Ukraine, 2018)
IX Congress of the Public Organization “Ukrainian Entomological Society” (general review, report of theAudit сcommission, Scientific Board of UES, resolution)